VD_FINDINFO Arrêt / 2014 / 420 vom 6. August 2014 - VD Tribunal cantonal (2014)
AIASSURANCE, ALCOOLISME, ATTEINTE À LA SANTÉ PSYCHIQUE, ATTEINTE À LA SANTÉ PHYSIQUE | 28 LAI, 4 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA